How to sustainably build capacity in quality improvement within a healthcare organisation: a deep-dive, focused qualitative analysis - Peter D. Hibbert; Martin Basedow; Jeffrey Braithwaite; Louise K. Wiles; Robyn Clay-Williams; Robert Padbury (BMC, 2021)
Abstract Background A key characteristic of healthcare systems that deliver high quality and cost performance in a sustainable way is a systematic approach to capacity and capability building for quality improvement. The aim of this research was to explore the factors that lead to successful implementation of a program of quality improvement projects and a capacity and capability building program that facilitates or support these. Methods Between July 2018 and February 2020, the Southern Adelaide Local Health Network (SALHN), a network of health services in Adelaide, South Australia, conducted three capability-oriented capacity building programs that incorporated 82 longstanding individual quality improvement projects. Qualitative analysis of data collected from interviews of 19 project participants and four SALHN Improvement Faculty members and ethnographic observations of seven project team meetings were conducted. Results We found four interacting components that lead to successful implementation of quality improvement projects and the overall program that facilitates or support these: an agreed and robust quality improvement methodology, a skilled faculty to assist improvement teams, active involvement of leadership and management, and a deep understanding that teams matter. A strong safety culture is not necessarily a pre-requisite for quality improvement gains to be made; indeed, undertaking quality improvement activities can contribute to an improved safety culture. For most project participants in the program, the time commitment for projects was significant and, at times, maintaining momentum was a challenge. Conclusions Healthcare systems that wish to deliver high quality and cost performance in a sustainable way should consider embedding the four identified components into their quality improvement capacity and capability building strategy.